Sureśvara's Vārtika on Puruṣavidha Brāhamaṇa - Jog, K. P.; Hino, Shoun (Motilal Banarsidass Publishers, 1993)
English translation with notes of a supercommentary on Śaṅkarācārya's Bhāṣya on Br̥hadāraṇyakopaniṣad.